Analyzing the Flow of Ideas in University Students’ Cause and Effect Essay - Prativi Khilyatul Auliya; Qadrina Lailyn Amrullah (INNOVATION RESEARCH JOURNAL, 2024)
This research was carried out to find out the unity, coherence, and organization on cause-and-effect essay composed by the fourth semester students of Welding Engineering Study Program in Politeknik Perkapalan Negeri Surabaya. This study employed content analysis in which students’ essay writings were analyzed to gain the data. The population comprised four classes, each consisting of approximately 30 students. The sampling process involved randomly selecting 3 essays from each class, resulting in a total sample size of 12 essays. The findings showed that among 12 essays, 4 essays were unified, and 8 essays were less unified. The unified essays fulfilled the following criteria; (1) clear thesis statement, (2) topic sentences, (3) consistent support, (4) coherence and transition, and (5) concluding paragraph. In addition, among the 12 essays, 4 were categorized as coherent, 7 less coherent, and 1 incoherent. The coherent essays could accomplish the following criteria; (1) using consistent nouns and pronouns, (2) using proper transition signals, (3) organizing topic in a logical sequence, (4) having unity, and (5) using connectors for linking ideas and paragraph. Nevertheless, 11 out of 12 essays showed that they had good organization, which consisted of introduction, body, and conclusion. Therefore, it can be concluded that most of students are able to compose cause and effect essay in well organized even though students still need guidance to compose unified and coherent essay.